Overlapping of Intestinal Tuberculosis with Typhoid Fever as Initial Diagnosis: A Case Report - Simatupang, Elvando Tunggul Mauliate; Simbolon, Rohani Lasmaria; Bet, Anwar; Makmur, Andreas; Simatupang, Elcia (Malang Respiratory Journal, 2024)
Background: Extrapulmonary Tuberculosis (ETB) cases have increased to 20-30% of all Pulmonary Tuberculosis (PTB) cases, including Intestinal Tuberculosis (ITB). Overlap between ITB and Typhoid Fever (TF) leads to Diagnostic Delays in ITB. Endoscopic and histopathological examinations are needed as diagnostic support, so comprehensive examination and clinical evaluation are necessary. Accurate diagnosis and management will have significant implications for patient survival. Case: A 23-year-old male patient complained of shortness of breath for three weeks. Previously fever, night shivering, loss of appetite, and weight loss were also experienced. A history of previous hospitalization involving abdominal colic complaints, the patient should be hospitalized twice. Repeated administration of antibiotics with TF diagnosis did not show any clinical improvement. The suspicion of ITB was proven after obtaining positive results from Genexpert (GE) of Faeces and clinical response after Anti Tuberculosis Drugs (ATD) administration. Overall, there were clinical, laboratory and radiological improvements in patients with clinical abdominal colic and fever experienced in the last 2 months. Conclusion: Challenge ATD delivery and GE of Faeces can be used as an indicator of suspects ITB so overlap between ITB and TF can be predicted. A comparative diagnostic study of abdominal colic and recurrent fever should also be extended so that it can be continued with several diagnostic support.